Breathless and awaiting diagnosis in UK lockdown for COVID-19…We’re stuck - Gillian Doe (Nature Portfolio, 2021)
Abstract During the COVID-19 pandemic, semi-structured interviews were undertaken with 20 adults awaiting a diagnosis for their chronic breathlessness. Three key themes were identified using thematic analysis: (1) de-prioritisation of diagnosis, (2) following UK ‘lockdown’ guidance for the general population but patients fearful they were more at risk, and (3) the impact of lockdown on coping strategies for managing breathlessness. The existing unpredictable pathway to diagnosis for those with chronic breathlessness has been further interrupted during the COVID-19 pandemic.